Downlink soft handover mechanism performance in WCDMA system - Ismail M.; Aripin N.; Ahmad N.; Ibrahim M.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
An in depth study of the soft handover effects on the downlink direction of WCDMA network is carried out The link level study begins with the downlink interference analysis and power allocations for each downlink dedicated channels. Downlink soft handover gain is used in the system level simulation as a main parameter to evaluate the effects of cell selection and power control mechanisms on the downlink soft handover performance. Simulation result has shown that by using 2-way soft handover mechanism, the required dedicated transmission power can be reduced up to 3dB. Besides that, the cell selection scheme based on distance and Ec/I0 value gives better SHO gain (1.3dB) to the system with SHO overhead equals to 30%. Simulation also has shown that the system can benefit from the soft handover process at 20% to 30% of the SHO overhead. However, power control mechanism does not give significant impact to the SHO gain.